Nutritional Studies of Different Cultivars of Dolichos lablab and Phaseolus vulgaris - Zaman, Absheen; Mahmood, Hamida Nooreen; Tushy, Tahfima Sultana; Haque, Md Enamul (Bangladesh Journal of Nutrition, 2019)
This article decribes the nutrient composition of different varieties of Dolichos lablab seeds and Phaseolus vulgaris seeds. In this experiment, nine different types of Dolichos lablab seeds and eight different types of Phaseolus vulgaris seed samples were analyzed for proximate composition, sugar, vitamins, and minerals content. Dolichos lablabs seeds contained 13.2%-16.1% moisture, 1.7%-3.45% ash, 0.6%- 1.39% total fat,16.58%-29.04% total protein, 6.85%-8.91% crude fiber, 51.66%-66.16% total carbohydrate,328.65-340.59 Kcal energy, 0.0172- 0.58% reducing sugars, 51.2-66.15% non-reducing sugars, 0.01-0.78% glucose, and 15.43-18.39% amylose. Phaseolus vulgaris seed contains 12.5%-14.9% moisture, 2.98%-5% ash, 0.49%- 14.9% total fat, 11.19%-29.04% total protein, 2.9%-3.6% crude fiber, 53.36%-71.10% total carbohydrate, 328.76-453.29 kcal energy, 0.05-0.51% reducing sugars, 53.174-70.643% non-reducing sugars, 0.01-0.32% glucose, and 6.43-18.47% amylose. Thiamine, niacin, pyridoxine, L-ascorbic acid content for Dolichos lablab seeds ranged 1.11-1.24 mg/100g, 1.53-1.67 mg/100g, 0.04-0.21 mg/100g, 5.52-11.06 mg/100g respectively. And for Phaseolus vulgaris, thiamine, niacin, pyridoxine, L-ascorbic acid content ranged 0.19-1.6 %, 2.2-2.38%, 0.24-1.7 %, 2.765-5.54 % respectively. Both Dolichos lablab and Phaseolus vulgaris contained good amount of minerals. Dolichos lablab contained phosphorus 374-500 mg, calcium 31.63-130.1 mg, copper 0.878-1.04 mg, iron 5.957-14.182 mg, magnesium 1377.16-2332.16 mg, manganese 0.19125-0.35875 mg, nickel 0.13-1.663 mg, zinc 3.89-6.61 mg, and cadmium 0.0013-0.025 mg. On the other hand, Phaseolus vulgaris contained phosphorus 362-584 mg, calcium 41.63-104.1 mg, copper 0.823-1.646 mg, iron 4.845-13.08 mg, magnesium 1462.16-1697.16 mg, manganese 0.1375-0.275 mg, nickel 0.215-5.463 mg, zinc 1.07-12.2 mg, and cadmium 0.0012-0.312 mg in it. Thus nutritional studies on beans could bring about important changes in our food habit in order to prevent many diseases related to nutritional deficiency. Bangladesh J. Nutr. Vol. 32, December 2019, P: 25-35